2007
DOI: 10.1016/j.immuni.2007.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Tyrosine Kinase Syk Is Necessary for E-Selectin-Induced αLβ2 Integrin-Mediated Rolling on Intercellular Adhesion Molecule-1

Abstract: Engagement of neutrophils by E-selectin results in integrin activation. Here, we investigated primary mouse neutrophils in whole blood by using intravital microscopy and autoperfused flow chambers. Slow rolling on E-selectin coimmobilized with intercellular adhesion molecule-1 (ICAM-1) required P-selectin glycoprotein ligand (PSGL)-1, was dependent on alpha(L)beta(2) integrin (LFA-1), and required continuous E-selectin engagement. Slow rolling was abolished by pharmacological blockade of spleen tyrosine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
410
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 266 publications
(442 citation statements)
references
References 60 publications
26
410
3
1
Order By: Relevance
“…Two hours after TNF-a injection, leukocyte rolling is mediated by P-selectin and E-selectin expressed on inflamed endothelial cells of the cremaster muscle (9,33). Galnt1 2/2 mice had a reduced rolling flux fraction on E-and P-selectin compared with control mice 2 h after TNF-a injection ( Fig.…”
Section: Short-term (2-h) Tnf-a-induced Inflammationmentioning
confidence: 94%
See 4 more Smart Citations
“…Two hours after TNF-a injection, leukocyte rolling is mediated by P-selectin and E-selectin expressed on inflamed endothelial cells of the cremaster muscle (9,33). Galnt1 2/2 mice had a reduced rolling flux fraction on E-and P-selectin compared with control mice 2 h after TNF-a injection ( Fig.…”
Section: Short-term (2-h) Tnf-a-induced Inflammationmentioning
confidence: 94%
“…To investigate whether the signal-transduction cascade is disturbed after E-selectin binding to PSGL-1, we performed an E-selectin-engagement assay to demonstrate intact downstream signaling. We already showed that Syk is phosphorylated after stimulating neutrophils with E-selectin (9). Therefore, we checked Syk phosphorylation in Galnt1 2/2 and control mice.…”
Section: Short-term (2-h) Tnf-a-induced Inflammationmentioning
confidence: 96%
See 3 more Smart Citations